EFEKTIVITAS PEMBELAJARAN TARI MENGGUNAKAN MEDIA MENTARI DALAM MENINGKATKAN KEMAMPUAN PSIKOMOTOR ANAK DOWN SYNDROME - Richa Madu Rena; Agung Kurniawan; Nabilla Kurnia Adzan (STKIP Subang, 2026)
This study aimed to examine the effectiveness of the Mentari media as a therapeutic tool in improving the Psychomotor abilities of children with Down Syndrome at PIK Potads Lampung. This research employed a quantitative method with a descriptive approach and a One Group Pretest–Posttest design. The research subjects were children with Down Syndrome who participated in a dance-based therapeutic learning program using Mentari media. The study was conducted over 18 learning sessions that were systematically designed to stimulate children's Psychomotor development through dance movement activities. The measurement of Psychomotor ability was based on three aspects: remembering movements, understanding movements, and applying movements, which refer to Bloom’s Taxonomy 2021. The results of the study showed an improvement in the Psychomotor abilities of the research subjects, indicated by an increase in the average score from 52.8% score 35.4 in the pretest to 125.6% score 83.7 in the posttest. The results of the t-test showed a significance value of 0.000 (p < 0.05), indicating that the alternative hypothesis (Ha) was accepted. These findings indicate a significant difference in psychomotor abilities before and after the implementation of dance learning using Mentari media. Therefore, it can be concluded that Mentari media is significantly effective as a therapeutic tool to improve the Psychomotor abilities of children with Down Syndrome at PIK Potads Lampung.